MAMMALS OF GAG ISLAND - Ibnu Maryanto; Darrell J. Kitchener (Treubia, 1999)
Gag island, with 13 species of mammal recorded from a brief survey of only 10 days, has a relatively rich mammal fauna for its area (56 km2). This mammal assemblage was more influenced by faunal elements from nearby Irian Jaya and North Maluku than from elsewhere. More intensive surveys on Gag island will undoubtedly reveal further species of small microchiropteran bats. Habitats on the ultrabasic substrates were richer, more diverse and overall had a higher relative abundance of bats than those on the volcanics. The period of the survey and immediately preceding it was one of intense breeding activity for most, or all, of the bat species and for Rattus sp. The taxonomic status of two still to be identified mammals, a murid rodent Rattus sp. and the Tube - nosed Bat (Nyctimene sp.) on Gag island require further clarification.